PENGARUH METODE BERMAIN KARTU KATA TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS 1 UPT SD NEGERI 69 GALESONG 1 - Sri Rahayu; Ainun Fitri Delila, Nurainung; Rifqah Fadilah, Wandi Eka Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve the early reading skills of Grade 1 students through the application of the word card game method at UPT SD Negeri 69 Galesong 1. This study employs a qualitative descriptive method with a classroom action research (PTK) design in one cycle. Data were collected through observation and early reading tests. The results show an improvement in students’ early reading skills, with an average score of 98.59 and 100% classical completeness. The use of word card media proved effective in helping students recognize letters, assemble syllables, and read words fluently. In addition, the enjoyable learning atmosphere through the game-based method enhanced students’ motivation, participation, and self-confidence. It can be concluded that the word card game method is an effective alternative learning media to improve early reading skills in Grade 1 students.